ChemInform Abstract: Acetylide Ion(C22‐) as a Synthon to Link Electrophiles and Nucleophiles: A Simple Method for Enaminone Synthesis. Issue 40 (12th September 2013) - Yu, Dingyi; Sum, Yin Ngai; Ean, Amanda Chng Cheng; Chin, Mei Ping; Zhang, Yugen
Abstract The three‐component reaction of aryl aldehyde, calcium carbide and a bulky secondary amine provides a direct synthesis of enaminones (IV).